Consistency in coral skeletal amino acid composition offshore of Palau in the western Pacific warm pool indicates no impact of decadal variability in nitricline depth on primary productivity - Branwen Williams; Benoit Thibodeau; Yoshito Chikaraishi; Naohiko Ohkouchi; Andrew Walnum; Andréa G. Grottoli; Patrick L. Colin (Limnology and Oceanography, 2017)
The depth of the thermocline and associated nitricline in the western Pacific warm pool (WPWP) vary over time in response to changes in larger ocean‐atmosphere climate patterns. A shoaling of the nitricline in the WPWP brings nitrate‐rich seawater ( > 4 μ mol kg −1 ) above the base of the euphotic zone, stimulating primary productivity. Here, we test if decadal variability in the nitricline depth is driving changes in regional primary productivity and source nitrate dynamics. We use the nitrogen isotopic composition (δ 15 N) of amino acids in the skeleton of a proteinaceous coral collected from the base of the euphotic zone in the WPWP. In proteinaceous corals, as in most organic life, the δ 15 N of phenylalanine matches that of the ambient nitrate while the δ 15 N of trophic amino acids reflect subsequent trophic transfer of the nitrogen prior to incorporation into the coral's food, suspended particulate organic matter. Consistency of the trophic position of the coral calculated from the δ 15 N composition of the coral skeletal amino acids over its 56 yr lifespan suggest that decadal variability in nitricline depth and subsequent shifts in nitrate availability to the euphotic zone have not impacted primary productivity offshore of Palau in the WPWP. This is important when considering the current external forcing of Pacific Ocean climate patterns and the resulting impacts on the global carbon cycle in the Palau region of the WPWP.